2019
DOI: 10.1039/c8dt03524e
|View full text |Cite
|
Sign up to set email alerts
|

Structural transformations of the La2−xPrxNiO4+δ system probed by high-resolution synchrotron and neutron powder diffraction

Abstract: Subtle structural distortions in the La2−xPrxNiO4+δ system are investigated using high resolution X-ray powder diffraction and neutron powder diffraction, analyzed by combined Rietveld refinements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 59 publications
2
9
0
Order By: Relevance
“…The X-ray diffractograms of La 2 NiO 4+d and Nd 2 NiO 4+d can be tted in the orthorhombic space group Fmmm, which is in good agreement with previous analyses of data from synchrotron Xray powder diffraction (SXRPD) and neutron powder diffraction (NPD) of both materials. 10,44,45 The XRD pattern of La 3 Ni 2 -O 7Àd can be tted in the orthorhombic space group Cmmm, consistent with the results from Mössbauer spectroscopy and XRD by Kiselev et al 46 The XRD patterns of the n ¼ 3 RP S1-S5. † All compositions are found to be phase-pure, i.e., no impurity peaks are observed up to 1000 C. Fig.…”
Section: Crystal Structure and Phase Transitionssupporting
confidence: 78%
See 1 more Smart Citation
“…The X-ray diffractograms of La 2 NiO 4+d and Nd 2 NiO 4+d can be tted in the orthorhombic space group Fmmm, which is in good agreement with previous analyses of data from synchrotron Xray powder diffraction (SXRPD) and neutron powder diffraction (NPD) of both materials. 10,44,45 The XRD pattern of La 3 Ni 2 -O 7Àd can be tted in the orthorhombic space group Cmmm, consistent with the results from Mössbauer spectroscopy and XRD by Kiselev et al 46 The XRD patterns of the n ¼ 3 RP S1-S5. † All compositions are found to be phase-pure, i.e., no impurity peaks are observed up to 1000 C. Fig.…”
Section: Crystal Structure and Phase Transitionssupporting
confidence: 78%
“…The cell parameters for all compositions are in good agreement with those reported previously in the literature. 5,10,41,[43][44][45][46][47] The crystallographic parameters obtained from the Rietveld renements are listed in Table S1. † The corresponding structures of the RP nickelates are shown in Fig.…”
Section: Crystal Structure and Phase Transitionsmentioning
confidence: 99%
“…The relatively high ADP value for the O1 site (Table 2) is not from signicant thermal motion of oxygen but likely from disordered oxygen ion displacements. 47,48 All oxygen positions are corner-shared sites of either vanadium or copper centered polyhedra, such as two VO 4 tetrahedra sharing O1 sites. Both O2 and O3 are shared between a VO 4 tetrahedron and a CuO 5 distorted square pyramid.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown a reasonably linear decrease in unit-cell volume with increasing chemical doping (x) in the solid solutions La 2−x Pr x NiO 4 and Pr 2−x Nd x NiO 4 (see Figure 5). 32,33 This is expected, as the ionic radii of the lanthanides decrease with increasing Z across the lanthanide series La (1.216 Å) > Pr (1.179 Å) > Nd (1.163 Å) (with ninefold coordination in 3+ oxidation state). It is possible to determine the equivalent pressure required to compress the parent (undoped) material to the same unit-cell volume using the EoS parameters determined for the end member.…”
Section: Chemical Vs Hydrostatic Pressurementioning
confidence: 79%